The Impact of Financial Technology on Student Investment Decisions - Sulasmiyati, Sri; Putri Nurhayati, Rizka Aprillia (Profit: Jurnal Adminsitrasi Bisnis, 2024)
Investment is an important aspect of financial planning for every individual. The public can more easily access current investment activities through financial technology. This study aims to find out what factors influence student interest in investing through financial technology. Those factors consist of perceived ease of use, perceived usefulness, perceived compatibility, investment knowledge, and trust in investment intention using financial technology. This study employed a quantitative methodology, specifically adopting an explanatory research design. Primary data was used and obtained by distributing online questionnaires to university students in Malang who have invested in financial technology, and 60 respondents were selected using purposive sampling. The data analysis technique used the Multiple Regression Analysis method. The results of this study showed that perceived ease of use, perceived compatibility, investment knowledge, and trust had a positive and statistically significant effect on investment intention using financial technology. The effect of perceived usefulness on investment intention using financial technology was positive but statistically not significant. It could happen because the data needs to need to provide sufficient evidence (due to the limited number of respondents) to confidently conclude that the observed positive effect is a reliable and meaningful pattern in the population being studied.